Studies on Neotropical Phasmatodea XXVI: Taxonomic review of Cladomorformia tax. n., a lineage of Diapheromerinae stick insects, with the descriptions of seven new genera and 41 new species (Phasmatodea: Occidophasmata: Diapheromerinae) - Hennemann, Frank H.; Conle, Oskar V. (Zootaxa, 2024)
Stick and leaf insects (Phasmatodea) are a moderately diverse order that comprises almost 3,500 extant species of large to very large often impressively camouflaged nocturnal herbivores. The order also stands out as one of the few insect orders that have until lately lacked a robust higher-level phylogeny and still the relationships between many New World taxa in particular remain unknown. The Diapheromerinae is one of the main lineages of the Occidophasmata and comprises a bulk of the diversity of New World stick insects. The clade is endemic to the Americas and includes the longest insects of that region. During the past 25 years Diapheromerinae has experienced various often inconsistent attempts of a classification, which have resulted in a complicated history that has meanwhile constituted a heterogenous mixture of historical and contemporary views. To counter these challenges workers have made use of rank-free taxa to provisionally group supposedly monophyletic clades. Currently the Diapheromerinae are sub-divided into the two tribes Diapheromerini and Oreophoetini and recent molecular analyses have shown taxa of the Cladomorphinae Günther, 1953 to belong to Diapheromerinae. Certainly, the clade still deserves much work to delimit meaningful sub-groups within Diapheromerinae reflective of their evolutionary history and the results of the latest comprehensive molecular-based phylogenetic studies already imply sub-divisions within the Diapheromerini. The rank-free taxon Cladomorformia tax. n. is established to comprise former Cladomorphini, Cranidiini, Otocrania Redtenbacher, 1908 as well as sections of Diapheromerini sensu Robertson et al., 2018, which are the genera that have previously been placed in the “Phanocles group” sensu Zompro, 2001 as well as two genera of the “Bacteria group” and one genus of the “Clonistria group”: Alienobostra, Bostriana, Calynda, Globocalynda, Laciphorus, Phanocles, Phanocloidea and Trychopeplus. The genus Cranidium and all genera of Cladomorphini sensu Hennemann et al., 2016 are here formally transferred to Diapheromerinae, this is Aplopocranidium, Cladomorphus, Jeremia, Jeremiodes, Otocraniella and Xylodus. A holistic review of Cladomorformia at the genus level is conducted herein and new diagnoses, differentiations and keys to all 25 genera that are now contained in that clade are presented. Lists of species are provided for all genera, which include detailed type data, synonymies and distributional records. Moreover, identification keys to all 163 known valid species are provided to render identification of species within the 25 known genera possible. In total, 232 species are covered if the 69 synonymous taxa are included. The subfamily Haplopodinae is introduced to comprise all genera of the tribes Haplopodini, Hesperophasmatini and Pterinoxylini as classified by Hennemann et al. (2016) as well as the recently described Teruelphasmini. Renaming former Cladomorphinae sensu Robertson et al. (2018) into Haplopodinae is necessary, because the type-genus Cladomorphus can no longer be considered a member of that lineage and belongs in Diapheromerinae. Haplopodinae is the only New World clade that belongs into the Old World Oriophasmata. Bostranova Villet, 2023 has been introduced to replace the preoccupied Bostra Stål, 1875. The type-species of Bostranova, Bacteria turgida Westwood, 1859, however is here shown to belong in Phanocloidea Zompro, 2001. Thus, Bostranova is synonymised under Phanocloidea (n. syn.) and all species are transferred to Phanocloidea and other genera. Paraphanocles Zompro, 2001 (Type-species: Mantis keratosqueleton Olivier, 1792) is synonymised with Phanocles Stål, 1875 (syn. n.). Seven new genera are described: Globocrania gen. n. (Type-species: Bacteria emesa Westwood, 1859), Hirtuleiodes gen. n. (Type-species: Phibalosoma gibbosa Chopard, 1911), Lanceobostra gen. n. (Type-species: Bacteria aetolus Westwood, 1859), Ocreatophasma gen. n. (Type-species: Ocreatophasma elegans sp. n.), Parotocrania gen. n. (Type-species: Parotocrania panamae sp. n.), Phanoclocrania gen. n. (Type-species: Bostra dorsuaria Stål, 1875) and Spinocloidea gen. n. (Type-species: Spinocloidea panamaense sp. n.). All seven genera are described from both sexes and the eggs, with the exception of Ocreatophasma gen. n., which is known from the females only. Forty-one new species are described: Globocalynda cornuta sp. n. from Ecuador, Globocalynda marcapatae sp. n. from Peru, Globocalynda ruficollis sp. n. from Bolivia, Hirtuleiodes peruanus sp. n. from Peru, Jeremiodes costaricensis sp. n. from Costa Rica, Jeremiodes ecuadoricus sp. n. from Ecuador, Jeremiodes peruanus sp. n. from Peru, Lanceobostra chapalaense sp. n. from Mexico, Lanceobostra glabra sp. n. from Mexico, Lanceobostra oaxacaee sp. n. from Mexico, Lanceobostra ornata sp. n. from Mexico, Lanceobostra torquata sp. n. from Mexico, Lanceobostra tuckerae sp. n. from Mexico, Ocreatophasma elegans gen. n., sp. n. from Peru, Ocreatophasma fragile gen. n., sp. n. from Peru, Ocreatophasma modestum gen. n., sp. n. from Peru, Parotocrania acutilobata gen. n., sp. n. from Ecuador, Parotocrania curvata gen. n., sp. n. from Peru, Parotocrania panamae gen. n., sp. n. from Panama, Phanocles acutecornutus sp. n. from Ecuador, Phanocles barbadosense sp. n. from Barbados, Phanocles berezini sp. n. from Mexico, Phanocles brevipes sp. n. from Peru, Phanocles chiapasense sp. n. from Mexico, Phanocles cuzcoense sp. n. from Peru, Phanocles ecuadoricus sp. n. from Ecuador, Phanocles falcatus sp. n. from Ecuador, Phanocles maximus sp. n. from Panama, Phanocles mexicanus sp. n. from Mexico, Phanocles pleurospinosus sp. n. from Costa Rica, Phanocles rehni sp. n. from Honduras, Phanocles solidus sp. n. from Ecuador, Phanocles spectabilis sp. n. from Costa Rica, Phanocles superbus sp. n. from Ecuador, Phanocloidea sanguinea sp. n. from Ecuador, Phanocloidea semiptera sp. n. from Venezuela, Phanocloidea venezuelica sp. n. from Venezuela, Spinocloidea panamaense gen. n., sp. n. from Panama, Spinocloidea splendida gen. n., sp. n. from Colombia and Spinocloidea tumescens gen. n., sp. n. from Costa Rica. With a maximum recorded body length of 285.0 mm the new species Phanocles maximus sp. n. from Panama is the longest extant insect of the Americas and the Occidophasmata clade. A total of 132 taxonomic changes are conducted: 64 species are transferred to other genera and 43 new synonyms are established. Lectotypes are designated for 25 taxa to ensure stability of the concerned names or new synonymies here established. Moreover, the previously unknown females of five and males of twelve species are described and illustrated for the first time. Colour illustrations are presented of the eggs of 39 species, of which those of 26 species are formally described and illustrated for the first time.